Ставка на проигрыш: роман / М. Я. Черненок - Черненок Михаил (Военные приключения, 2011)
Экземпляры: аб. (2012) / Инвентарный номер: 54127 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Ч-49 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44